2013
DOI: 10.11002/kjfp.2013.20.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Change in quality attributes of fresh-cut potatoes with heat and browning inhibitor treatment during storage

Abstract: This study was conducted to investigate the change in quality attributes of fresh-cut potatoes with heat and browning inhibitor treatment (CW: dip in the cold water for 30 sec at 4℃, HW: dip in the water for 60 sec at 55℃, AA: dip in the 0.1% solution of ascorbic acid for 60 sec at 4℃, HA: dip in the 0.1% solution of ascorbic acid for 60 sec at 55℃) during storage at 5℃. During storage, fresh-cut potatoes treated with HA showed the lowest value in surface color. PPO and PAL activities of fresh-cut potatoes tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Turbidity was higher in the NF15 and NF20 (1.06, 1.02) than in the CON (0.73; P < 0.05). It seems that potato garaetteok was easily dissolved in water, while being cooked as potato starch gel is smooth and springy but the gel strength is weak [32]. In contrast, the turbidity was significantly lower in BS and LM groups than in the NF group (P < 0.05).…”
Section: Texture Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Turbidity was higher in the NF15 and NF20 (1.06, 1.02) than in the CON (0.73; P < 0.05). It seems that potato garaetteok was easily dissolved in water, while being cooked as potato starch gel is smooth and springy but the gel strength is weak [32]. In contrast, the turbidity was significantly lower in BS and LM groups than in the NF group (P < 0.05).…”
Section: Texture Propertiesmentioning
confidence: 91%
“…e first browning reaction occurs by PAL to generate phenolic compounds. ese act as a substrate for PPO to catalyze the oxidation, which cause browning at the cut surface of fruits and vegetables compounds [31,32]. e addition of potato flour to rice garaetteok significantly increased the a * value of redness and b * value of yellowness (P < 0.05).…”
Section: Chromaticitymentioning
confidence: 99%
“…The smallest increase in TSS (from 4.36 to 5.31%) was observed in T3 (dices), whereas the largest increase (4.38-5.75%) was found in T1 (slices), during the entire cold storage period (Table 1). Song et al (2013) claimed that fresh-cut potato treated with AA solution showed an increasing trend in TSS, and Nourian et al (2003) observed that the TSS of potato increased during storage.…”
Section: Total Soluble Solids (Tss)mentioning
confidence: 99%
“…During the 60 days of cold storage, the largest WL (from 0 to 11.47%) was observed in T1 (slices) and the smallest (0 to 9.04%) was verified in T3 (dices) due to the smaller surface area exposed to the air (Table 1). Bico et al (2009) found that chemically dipped fresh-cut banana showed less WL than the untreated samples, and Song et al (2013), studying fresh-cut potato treated with an anti-browning agent, reported increased WL during storage.…”
Section: Weight Loss (Wl)mentioning
confidence: 99%
See 1 more Smart Citation